Abundance and size-frequency distribution of boulders in Linné crater's ejecta (Moon). (January 2019) - Pajola, Maurizio; Pozzobon, Riccardo; Lucchetti, Alice; Rossato, Sandro; Baratti, Emanuele; Galluzzi, Valentina; Cremonese, Gabriele
Abstract: This paper presents the abundances and the size-frequency distributions (SFD) of the ejected boulders surrounding the Linnè crater, located on the Moon's Mare Serenitatis basin. By means of Lunar Reconnaissance Orbiter Camera high-resolution images we prepare a context geological map of the Linné crater as well as we identify ∼ 12000 boulders ≥4.4 m, with a maximum measured size of 30.8 m. The cumulative number of boulders per km 2 is fitted with a power-law curve with index −4.03 + 0.09/-0.10. By studying the radial ejecta abundances, we find that the largest ones are located within the first 2 km from the crater's centre, while few tens of boulders with sizes < 8 m are detectable above 5 km from the crater's rim. We find that the Linné proximal ejecta blanket is slightly asymmetrical, as indicated in the geological map too, showing a density increase in the NE-SW direction. This may be the result of an oblique impact emplacement of the original impactor, or it may be explained with a perpendicular impact in the Mare Serenitatis location, but on a surface with lunar basalts with different local mechanical properties. By exploiting our boulders size density as a function of the distance from the crater's centre, we derive a possible regolith thickness at the Linnè impact of ∼4.75 m, supporting similar values based on Earth-based radar and optical data in the Mare Serenitatis basin. Highlights: High-resolution geological map of the Linné crater. Boulder SFD fitted with a power-law curve with index −4.03 + 0.09/−0.10, inside the lunar impact cratering formation ranges. Steepening of the boulder SFD power-law index with the distance from the Linné's rim. Linné proximal ejecta blanket slightly asymmetrical in the NE-SW direction. Regolith thickness at the Linné impact site in Mare Serenitatis of 4.75 m.